The Shan people's health beliefs, knowledge and perceptions of dengue in Eastern Shan Special Region IV, Myanmar. - Jian-Wei Xu; Hui Liu; Didan Ai; Yan Yu; Bian Yu (Public Library of Science (PLoS), 2019)
Sustainable dengue intervention requires the participation of communities. Therefore, understanding the health beliefs, knowledge and perceptions of dengue among the local people can help to design locally appropriate strategies for effective interventions. A combination of qualitative semi-structured in-depth interviews (SDIs) and quantitative household questionnaire surveys (HHSs) was used to investigate the beliefs, knowledge and perceptions of dengue among the Shan people in Eastern Shan Special Region IV (ESSR4), Myanmar. The SDI was administered to 18 key informants, and the HHS was administered to 259 respondents. Only 14.7% (95% CI: 10.6-19.6%) of the HHS respondents could confirm that mosquitoes transmit dengue; 14.3% (95% CI: 10.3-19.1%) knew that piebald or Aedes mosquitoes transmit dengue; and 24.3% (95% CI: 19.2-30.0%) believed that dengue-transmitting mosquitoes mainly lived in small ponds. Merely ten (0.4%) of the 259 respondents of the HHS thought that dengue-transmitting mosquitoes bite in the day time. The people in the villages where there were outbreaks of dengue had more knowledge about dengue. This study demonstrates that the health beliefs of the Shan people were closely associated with their lifestyles, social and natural environments. To stay healthy, the Shan people clean their houses and surroundings regularly. However, their knowledge about dengue was not adequate for effective dengue control because it was mostly learned from previous dengue experiences and in a context that lacks systematic health education. Thus, in this setting, with a weak public health structure, more international support should be provided to promote the knowledge of the Shan people about dengue and to increase their sensitive awareness to dengue, which might be beneficial for social mobilization and community participation during future dengue prevention.